Fecal microbiota transplantation for refractory immune checkpoint inhibitor-associated colitis. (December 2018) - Wang, Yinghong; Wiesnoski, Diana; Helmink, Beth; Gopalakrishnan, Vancheswaran; Choi, Kati; DuPont, Hebert; Jiang, Zhi-Dong; Abu-Sbeih, Hamzah; Sanchez, Christopher; Chang, Chia-Chi; Parra, Edwin; Francisco-Cruz, Alejandro; et al.
Abstract We report the first case series of immune checkpoint inhibitors (ICI)-associated colitis successfully treated with fecal microbiota transplantation, with reconstitution of the gut microbiome and a relative increase in the proportion of regulatory T-cells within the colonic mucosa. These preliminary data provide evidence that modulation of the gut microbiome may abrogate ICI-associated colitis. Preliminary evidence from two cases suggests that fecal microbiota transplantation may provide a viable treatment option for a severe adverse effect of immune checkpoint blockade therapy in patients with cancer.